PENDIDIKAN NILAI KARAKTER DI MIN MALANG 1 (Upaya Mengokohkan Kembali Peran Madrasah Sebagai Basis Penanaman Karakter) - Kamal, Rahmat (IAIN Pekalongan, 2012)
The essence of education is essentially not merely a matter of the transfer of knowledge, but also the transfer of values, in the sense that values instilment and those practices will be very significant in the formation of students’ noble and good character, not only just simply memorizing and knowing. Character education becomes a very urgent matter to be discussed and further developed both in the theoretical framework as well as the practical one, therefore teachers and educators have a clearer image and deeper knowledge from an institution’s experiences which continuously does the expansion in the implementation of education in order to achieve students’ good character. The problems presented in this study are: (1) how is the implementation of character education in Malang MIN 1?; (2) What are the values dominating?; (3) What are the tools of control of character education in MIN Malang 1? The purposes of this study are: (1) to understand the process of implementation of the character education in Malang MIN 1, (2) to find the values of characters instilled, and (3) to know the evaluation tool used in the character education in MIN Malang 1. This study is a field research within a qualitative approach. The subjects of this research are the head of the madrasa, deputy head of the madrasa, teacher representatives, and student representatives. The process of data collection is done by means of observation, interviews, and documentation. The process of data analysis include: observation, interviews, and documentation. The data analysis process covers: data reduction, data presentation, and data clarification and verification. The results showed that , first, the implementation of the character education in Malang MIN 1 basically represents the development of education of akhlak al - Karimah implemented in several aspects, namely : (a ) curriculum , ( b ) the madrasa culture , and ( c ) self-development program. Second, the values of the dominant characters seen in the students of MIN Malang 1, are: the values of disciplines, religiousness, and appreciation of performance. Third, the evaluation measurement of character education in MIN Malang 1 are: Teacher’s Diary (Anecdot Record), Case Book, and Counseling Book Report (BK).